Surgical cancer patient's perceptions of nursing care - Theodosopoulou, Eleni; Kaklamanos, Ioannis; Bonatsos, Gerasimos; Sarafis, Pavlos (My University, 2013)
The presentation of surgical cancer patients‟ perceptions of nursing care
Keywords: Cancer patients; Nursing care